The Prognostic Value of Calcium in Post-Cardiovascular Surgery Patients in the Intensive Care Unit - Bi, Siwei; Liu, Ruiqi; Li, Jingyi; Chen, Shanshan; Gu, Jun (Frontiers in Cardiovascular Medicine, 2021)
Background: Present researches exploring the prognosis value of calcium concentration are undermined by sample size and study design. Our study investigated the association of both total calcium (tCa) and ionized Ca (iCa) to short- and long-term mortality and other outcomes in post cardiovascular surgery (PCS) patients admitted to intensive care unit (ICU) from two large public datasets. Methods: The Medical Information Mart for Intensive Care III (MIMIC-III) database and the eICU Collaborative Research Database (eICU), were inspected to identify PCS patients. The primary outcome was 28-day mortality. Multivariate regression was used to elucidate the relationship between calcium concentration and outcomes. The propensity score estimation was performed to validate our findings. Results: A total of 6122 and 914 patients were included from MIMIC III and eICU datasets respectively. The groups with most patients were mild hypo-iCa and hypo-tCa groups. The mild hypo-iCa group showed significant association with worse short-term and long-term prognosis, less use of ventilation, longer ICU and hospital stay, more incidence of 7-day acute kidney injury. Conclusions: The mild hypo-iCa (0.9-1.15 mmol/L) within the first day admitted to ICU could serve as an independent prognosis factor of PCS patients.